Development Realistic LKPD on Exponential Material to Improve Grade X Students' Ability to Think Critically - Uday, Muhammad Ali; Handayani, Ucik Fitri (Program Studi Pendidikan Matematika Universitas PGRI Kanjuruhan Malang, 2025)
The aim of this study is to produce realistic mathematics education (RME)-based learner worksheets (LKPD) on exponent material to improve critical thinking skills of grade X students that are valid, practical and effective. The method used is Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation and evaluation. The results showed that the realistic based LKPD on exponent material was very valid based on the results of expert validation with a score of 87.5%, the practicality of realistic-based LKPD learning media was considered practical based on teacher and student responses with a score of 79.7%. In addition, its effectiveness can be seen from the increase in student learning outcomes with an average post-test score of 85.38%. The statistical test results show a significance value of 0.001 (two-tailed), indicating a significant difference between the pre-test and post-test results. Therefore, it can be concluded that the development of realistic-based worksheets improves students' critical thinking skills. The Realistic Mathematics Education approach links mathematical concepts to real-life situations, motivating students and helping them to understand exponential material more deeply. This study makes a valuable contribution to mathematics education by improving students' analytical and reasoning skills and facilitating a more meaningful, contextualised learning of exponents.